EFFECTS OF CLEANING METHODS ON NATA-DE-COCO MEMBRANE CHARACTERISTICS - Sudradjat ( NIM : 105 03 020), Felicia
Abstract : Nata-de-coco is a bacterial cellulose produced from the fermentation of coconut water by Acetobacter xylinum. The fermentation has been done for 4 days with sugar, glacial acetic acid, and ammonium sulfate as additional nutrients. Previous studies showed that chemical cleaning of nata-de-coco did affect the characteristics of the resulting membranes. Therefore, the effects of other cleaning method such as ultrasonic on the characteristics of nata-de-coco membranes has been studied in this work. A cleaning method by 1% (w/v) NaOH for 24 hours has been used for comparison, while the variation of ultrasonic cleaning time was 0.5; 1 and 1.5 hours. The characterizations of the resulting membranes included permeability, selectivity of dextran, mechanical strength, and morphology analysis by Scanning Electron Microscopy (SEM). The results showed that at 2 bars, the water flux of membrane cleaned by ultrasonic for 1 hour was similar to that of NaOH cleaning which was 26.09 L/m2. The rejection coefficients towards dextran T-70, T-500, and T-2000 of membranes cleaned by both methods did not differ significantly. The morphology analysis showed that 1.5 hours cleaning time made the surface of membranes became very rough and the cross-section of membranes was very dense. Nata-de-coco membranes cleaned by 1 hour ultrasonic showed the highest Youngs modulus, i.e. 3144 MPa. From all the membrane characteristics, it can be concluded that the 1 hour ultrasonic cleaning method gave similar results as the ones of NaOH cleaning method.